EDUKASI CINTA RUPIAH DALAM RANGKA MENCIPTAKAN MASYARAKAT PEDULI PEMBANGUNAN DI PASAR PASIA NAN TIGO KOTA PADANG - Yessy Andriani; Indrawari Indrawari; Laksmi Dewi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
The high cost of printing money is a significant burden on the economy. The leading cause is the lack of public awareness in treating rupiah currency properly so that the money becomes easily damaged (not fit for circulation). If it is damaged, the money must be printed again. The more money is damaged, and the faster the damage occurs, the higher the cost of printing money. Traditional markets have significantly contributed to the acceleration of the destruction of money, especially wet markets such as fish markets. This activity aims to disseminate and educate fish traders about the importance of caring for and treating money well through the